Identification of arsenic hyperaccumulating plants for the development of phytomitigation technology - H. Mirza, M.O. Gani Molla, M.A. Islam (Journal of Phytology, 2009)
Out of 35 plant samples collected from different districts of Bangladesh, only 14 species were arsenic (As) hyper accumulating. Species identified as hyperaccumulating were barnyard grass, water cress, cockle bur, Azolla, rice, water lettuce, water taro, taro, fern, water hyacinth and alligator weed. Maximum accumulation of As was in barnyard grass at 61.3 ppm, 67.9 ppm and 67.8 ppm in root, shoot and grain, respectively. From the chemical analysis of 35 naturally grown plants barnyard grass can mitigate soil As contamination. Water hyacinth, water cress, water lettuce and Azolla were able to absorb As from contaminated stagnant water. From this study an idea for phytoremediation of As by naturally grown plants has been found.